The Role of Entrepreneurship Education, Attitude Toward Risk and Digital Literacy on Entrepreneurial Intention Among Gen Z - Utami, Budi; Ibrahim, Mozart Malik; Violin, Vivid; Subroto, Desty Endrawati; Destari, Dina; Astuti, Enny Diah (Journal of Social Science and Business Studies, 2025)
This study aims to test and analyze the influence of entrepreneurship education, attitude toward risk and digital literacy on entrepreneurial intention, especially for generation Z. The researcher conducted a structured study of the results of studies that have been conducted by previous researchers, the results of the study discuss the determinant factors of entrepreneurial intention. The results of the studies analyzed were in the form of articles published in scientific journals over the past five years. The independent variables in this study are entrepreneurship education, attitude toward risk and digital literacy. The vocal or dependent variable in the study is entrepreneurial intention. The results of the analysis show that entrepreneurship education, attitude toward risk and digital literacy have a positive effect on entrepreneurial intention. The suggestion given is that the government should make policies related to education that support the development of the entrepreneurial ecosystem in Indonesia. The suggestion for managers of educational institutions is to introduce positive things about entrepreneurship to generation Z students as early and as often as possible.